Outpatient waiting time and patient satisfaction: A systematic literature review - Sinar Sinar; Nur Hidayah; Wahdaniah Wahdaniah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Outpatient waiting time is a key quality indicator that significantly influences patient satisfaction. Waiting times exceeding 60 minutes, as stipulated by the Minimum Service Standards (SPM), have been associated with reduced patient satisfaction and a decline in perceived healthcare service quality. Purpose: To map and synthesize scientific evidence regarding the relationship between outpatient waiting time and patient satisfaction across various healthcare facility settings. Method: This study employed a literature review design. Relevant articles were identified through systematic searches of electronic databases, including PubMed, Scopus, Garuda, CINAHL, Medline, and Google Scholar. Studies published between 2020 and 2025 that examined the association between outpatient waiting time and patient satisfaction were included. The selected studies were critically reviewed and narratively synthesized to identify patterns of findings and factors influencing the relationship between waiting time and satisfaction. The article selection process followed the PRISMA framework, resulting in 22 articles included for thematic analysis. Results: The findings indicate that outpatient satisfaction generally decreases as waiting time increases. This relationship is influenced by patient-related factors, including individual perceptions, expectations, and the availability of information regarding waiting processes. In addition, organizational and service-related factors, such as limited healthcare personnel, high patient volume, and inefficient service delivery systems, contribute to prolonged waiting times and reduced satisfaction. Conclusion: Waiting times that comply with Minimum Service Standards (≤60 minutes) are consistently associated with higher outpatient satisfaction. Effective waiting time management should not only focus on reducing actual waiting duration but also on managing patient expectations through clear communication and adequate information provision.